STRATEGI PENINGKATKAN MUTU PENDIDIKAN PADA ERA DIGITAL DI PONDOK PESANTREN TANBIHUL GHOFILIIN BANJARNEGARA - Ni’mah, Zuliana Fauzun; Amin, Samsul Munir (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2023)
This research is about strategies for improving the quality of education in the digital era at the Tanbihul Ghofiliin Banjarnegara Islamic boarding school. This research is a type of field research using a qualitative approach, where data is obtained through interviews, observations and documentation, then analyzed qualitatively including four steps, namely: editing data, classifying, analyzing and concluding. Research findings indicate that strategies for improving the quality of Islamic boarding schools in the digital era include several concrete steps: improving the quality of human resources, providing facilities and infrastructure; developing learning methods in formal schools and Islamic schools (non-formal), strengthening digital media; empowering alumni; and collaborating with other institutions. Referring to the theory of quality standards, this strategy aligns with the vision, mission, and goals of Islamic boarding schools, namely to produce multi-talented and noble students. This strategy has had an impact on the progress of Islamic boarding schools and increased public interest